Cubic GaN/AlN multi‐quantum wells grown on pre‐patterned 3C‐SiC/Si (001). Issue 2 (20th January 2014) - Kemper, R. M.; Mietze, C.; Hiller, L.; Stauden, T.; Pezoldt, J.; Meertens, D.; Luysberg, M.; As, D. J.; Lindner, J. K. N.
Abstract We report for the first time on the growth of cubic AlN/GaN multi‐quantum wells (MQWs) on pre‐patterned 3C‐SiC/Si (001) substrates. The sample structure consists of 10 periods of 2 nm c‐AlN barriers with a 4 nm c‐GaN layer in between, which were grown on 3C‐SiC post shaped structures by means of molecular beam epitaxy. Substrate patterning has been realized by electron beam lithography and a reactive ion etching process. The 3C‐SiC posts have a length of about 550 nm and a height of about 700 nm. (Scanning) transmission electron microscopy studies show that the morphology of the MQWs is clearly influenced by {111} stacking faults, modulating the local growth rate. Further, the growth at the edges of the surface pattern is investigated. The MQW layers cover the 90° edges by developing low‐index facets rather than by forming a conformal system of 90° angled layers. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)